2013
DOI: 10.1016/j.prevetmed.2013.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of veterinarians in bovine practice and producers with beef cow-calf operations enrolled in the US Voluntary Bovine Johne's Disease Control Program concerning economic losses associated with Johne's disease

Abstract: This study compares the perceptions of producers and veterinarians on the economic impacts of Mycobacterium avium subspecies paratuberculosis (MAP) infection in cow-calf herds. Questionnaires were mailed to beef producers through the Designated Johne's Coordinators and to veterinarians belonging to a nationwide professional organization. Important components of losses associated with MAP infected cows were used to estimate total loss per infected cow-year using an iterative approach based on collected survey d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Chi et al (2002) reported a total cost of $49.24 per cow for a 50-cow dairy herd with an apparent within-herd prevalence of 7%, while Tiwari et al (2008) reported a total cost of $49.05 per cow for a 61-cow dairy herd with an apparent prevalence of 12.7%. Our findings fall within similar ranges to those published from the United States (Can$21 to Can$43/cow; Ott et al, 1999;Bhattarai et al, 2013) and the UK (Can$41.65/cow; Gunn et al, 2004). Some of the primary differences observed relate to other models considering mortality and reproductive losses due to MAP infection, where our model did not.…”
Section: Discussionsupporting
confidence: 92%
“…Chi et al (2002) reported a total cost of $49.24 per cow for a 50-cow dairy herd with an apparent within-herd prevalence of 7%, while Tiwari et al (2008) reported a total cost of $49.05 per cow for a 61-cow dairy herd with an apparent prevalence of 12.7%. Our findings fall within similar ranges to those published from the United States (Can$21 to Can$43/cow; Ott et al, 1999;Bhattarai et al, 2013) and the UK (Can$41.65/cow; Gunn et al, 2004). Some of the primary differences observed relate to other models considering mortality and reproductive losses due to MAP infection, where our model did not.…”
Section: Discussionsupporting
confidence: 92%
“…This list is likely not exhaustive, perhaps due to a lack of representation from certain countries, or as Nielsen noted, a lack of knowledge and available literature on these programmes (Nielsen, ). The main drivers for adoption of these mostly voluntary on‐farm programmes are potential direct and indirect economic benefits to the agricultural from improved animal health and productivity and perceived enhanced product quality from M. paratuberculosis ‐free sources (Sorge et al., ,b; Bhattarai et al., ). Many of these on‐farm programmes focus on management recommendations to reduce the spread of infection among ruminants (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Reminder post-cards were mailed 8 days after the questionnaire. Additional details on questionnaire development and administration have been described elsewhere [15]. …”
Section: Methodsmentioning
confidence: 99%